Reflections about legislation and public policies regarding to adolescent health - Araújo, Yana Balduíno de; Gomes, Isabelle Pimentel; Collet, Neusa; Nóbrega, Rosenmylde Duarte da (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objective: to bring thoughts about public policies and legislation regarding adolescent health. Methodology: narrative literature review, built by bibliographical and documentarian research. We searched in LILACS, SciELO, BDENF and ADOLEC bases, from 2005 to 2009. The descriptors used: adolescent, public policy, health policy, adolescent health. The sample was composed of eleven articles and nine documents. Results: in 1985, WHO announced the international year of youth and Brazil was signatory, inferring in a national policy reorientation. Since then, there has been changes that influenced positively the construction of a governmental policy for health for teenagers. Its highlights were: promulgation of the Federal Constitution in 1988, creation of adolescent health program in 1989, institution of The Statute of Children and Adolescents in 1990. Even with rights established along this documents, essential to subside a qualified assistance to hospitalized adolescents, we observed that such rights are frequently violated or poorly respected. Conclusion: it´s believed that the practice of health regulations will be held if health professionals be aware of then, encouraging to demand its execution by the health institutions. Descriptors: adolescent; adolescent health; legislation; health policy; public policies. RESUMO Objetivo: refletir acerca da legislação e de políticas públicas voltadas à saúde do adolescente. Metodologia: revisão narrativa da literatura, construída por pesquisa bibliográfica e documental. Buscou-se nas bases SciELO, LILACS, BDENF e ADOLEC, no período de 2005 a 2009. Utilizou-se os descritores: adolescente, políticas públicas, política de saúde, saúde do adolescente. A amostra foi constituída por onze artigos e nove documentos. Resultados: 1985 foi o ano Internacional da Juventude pela OMS. O Brasil foi signatário, repercutindo na política nacional. Desde então, houve marcos que influenciaram positivamente a construção das políticas de saúde para o adolescente, destacam-se: 1988, promulgação da Constituição Federal; 1989, criação do Programa de Saúde do Adolescente; 1990, criação do Estatuto da Criança e do Adolescente. Mesmo com direitos apreendidos nos documentos, imprescindíveis para subsidiar uma assistência qualificada ao adolescente hospitalizado, destaca-se que tais direitos parecem ser violados com frequência, ou pouco respeitados. Conclusão: acredita-se que a prática das leis ocorrerão se os profissionais de saúde conhecê-las, sensibilizarem com a situação e com isso passem a exigir condições para o seu cumprimento junto aos dirigentes das instituições. Descritores: adolescente; saúde do adolescente; legislação; política de saúde; políticas públicas. RESUMEN Objetivo: Reflejan acerca de la legislación y políticas públicas de la salud de los adolescentes. Metodologia: Revisión narrativa, construida por búsqueda en la literatura y documentos. Utilizó las bases SciELO, LILACS, BDENF y ADOLEC, de 2005 la 2009. Utilizó los descriptores: adolescentes, políticas públicas, política de salud, salud del adolescente. La muestra consta de once artículos y nueve documentos. Resultados: En 1985 la OMS anunció el Año Internacional de la Juventud. Brasil fue firmado, lo que refleja la reorientación de la política nacional. Influyeron en la construcción de las políticas de salud para adolescentes, señala: en 1988 Constitución Federal, en 1989 Programa de Salud del Adolescente, en 1990 Estatus de la Niñez y la Adolescencia. Aunque los derechos son incautados en los documentos, fundamentales para apoyar una atención de calidad a los adolescentes hospitalizados, hace hincapié en que esos derechos parecen ser violados con frecuencia, o poco de respeto. Conclusión: la práctica del derecho se producirá si los profesionales sanitarios conocen y son conscientes de la situación y exigir a los jefes de las instituciones las condiciones adecuadas para cumplir las leyes. Descriptores: adolescente; salud del adolescente; legislación; política de salud; políticas públicas.